THE LEGITIMACY OF THE SALE AND PURCHASE CONTRACT OF SACRIFICIAL ANIMALS IN CURUP COMMUNITY - Dedi, Syarial; Lendrawati, Lendrawati (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2021)
This research is triggered from the qurban committee in Curup community to collect funds from the qurban participants by fixing the price of animals. The payment can be all at once and can also be paid in installments every month. This means buying and selling, even though the animals do not exist yet. After the money was collected and it was close to the sacrifice day, the committee went looking for an animal and then bought it. The role of the committee that made the sale and purchase contract was not the owner of the money. There is also buying and selling through brokers, who are not animal owners. Therefore, the main issue in this research concerns the validity of the contract for the sale and purchase of that qurban animals. This is a field research with qualitative approach. This study concluded that the implementation of the contract in muamalah transactions is elastic, especially in the oral form of al-ahwal. This is strongly influenced by the local community customs based on the rule of al-’adah muhakkamah.الملخصخلفية هذا البحث هي عمل لجنة الأضحية في مجتمع Curup لجمع الأموال من المشاركين في الأضحية من خلال تحديد أسعار الحيوانات. يمكن أن يكون الدفع دفعة واحدة ويمكن أيضًا سداده على أقساط كل شهر. هذا يعني البيع والشراء ، على الرغم من عدم وجود الحيوانات بعد. بعد أن تم جمع المال وقرب يوم الأضحية ، ذهبت اللجنة للبحث عن حيوان ثم اشترته. لم يكن دور اللجنة التي أبرمت عقد البيع والشراء هو صاحب المال. هناك أيضًا بيع وشراء من خلال سماسرة ليسوا من أصحاب الحيوانات. المشكلة الرئيسية في هذا البحث هي حول صحة عقد بيع وشراء حيوانات القربان. هذا البحث هو بحث ميداني بنهج نوعي. خلصت هذه الدراسة إلى أن تنفيذ العقد في معاملات المعامله مرن ، لا سيما في الشكل الشفهي للأحول. هذا متأثر بشدة بعادات المجتمع المحلي كصوت قواعد محاكمة العدة.